Instrumen Suplemen Konversi (ISK) Perguruan Tinggi : Conversion Supplements Instruments (ISK) for Higher Education - Markus Oci (Jurnal Teologi Amreta (ISSN: 2599-3100))
Implementation of tertiary accreditation is the assessment and recognition of the quality and performance of an institution. The Conversion Supplement Instrument (ISK) is an additional accreditation instrument used for decision making on the conversion of an accredited ranking obtained by the Standard 7 College Accreditation Instrument to a new accreditation rating in accordance with the Higher Education Accreditation 3.0 instrument. This research uses a qualitative method (Qualitatitive Research), with a literature study approach. What is meant by library research (Library Research) the author seeks information that is relevant to the subject matter. Higher Education Conversion Supplement (ISK) instruments consist of: front page, university identity, team identity preparation of ranking conversion report, preface, format of conversion supplement instrument (permanent lecturer, temporary lecturer, higher education quality assurance system, cycle internal quality assurance system, exceeding SN-PT, quality assurance mechanisms leading to Outcome Based Accreditation for accreditation of study programs and scientific publications. === Pelaksanaan akreditasi perguruan tinggi adalah penilaian dan pengakuan tentang kualitas dan kinerja suatu institusi. Instrumen Suplemen Konversi (ISK) adalah instrumen akreditasi tambahan yang digunakan untuk pengambilan keputusan konversi peringkat terakreditasi yang diperoleh dengan Instrumen Akreditasi Perguruan Tinggi 7 Standar menjadi peringkat akreditasi baru sesuai dengan instrumen Akreditasi Perguruan Tinggi 3.0. Penelitian ini menggunakan metode kualitatif (Qualitatitive Research), dengan pendekatan studi pustaka. Yang dimaksudkan dengan studi pustaka (Library Research) penulis mencari informasi yang relevan dengan pokok pembahasan. Instrumen Suplemen Konversi (ISK) perguruan tinggi terdiri dari: halaman depan, identitas perguruan tinggi, identitas tim penyusunan laporan konversi peringkat, kata pengantar, format intrumen suplemen konversi (dosen tetap, dosen tidak tetap, sistem penjaminan mutu perguruan tinggi, siklus sistem penjamian mutu internal, pelampauan SN-PT, mekanisme penjaminan mutu menuju Outcome Based Accreditation akreditasi program studi dan publikasi ilmiah.